Low-dose ionizing irradiation triggers a 53BP1 response to DNA double strand breaks in mouse spermatogonial stem cells. (3rd March 2016) - Le, Wei; Qi, Lixin; Li, Jiaxuan; Wu, DengIong; Xu, Jun; Zhang, Jinfu
ABSTRACT: The present study aims to examine the effect of low-dose ionizing irradiation on DNA double strand breaks (DSB) in mouse spermatogonial stem cells (SSCs) and reveal the underlying pathways for the DNA repair for DSB in SSCs. Eighteen one-month-old mice were divided into 6 groups and sacrificed separately at 45 minutes, 2 hours, 24 hours, 48 hours, and 72 hours after 0.1Gy X-ray irradiation (mice without receiving ionizing irradiation served as control). After perfusion fixation, testes were removed, sectioned, and followed by staining of γH2AX, 53BP1, Caspase 3, and promyelocytic leukemia zinc-finger (PLZF) for analysis among the different groups. The staining was observed by immunofluorescence visualized by confocal laser scanning. After low-dose irradiation, only 53BP1, but not Caspase3 or γH2AX was upregulated in PLZF positive SSCs within 45 minutes. The expression level of 53BP1 gradually decreased 24 hours after irradiation. Moreover, low-dose irradiation had no effect on the cell number and apoptotic status of SSCs. However other spermatogenic cells highly expressed γH2AX shortly after irradiation which was dramatically reduced following the events of DNA repair. It appears that low-dose ionizing irradiation may cause the DNA DSB of mouse spermatogenic cells. 53BP1, but not γH2AX, is involved in the DNA repair for DSB in SSCs. Our data indicates that 53BP1 plays an important role in the pathophysiological repair of DNA DSB in SSCs. This may open a new avenue to understanding the mechanisms of DNA repair of SSCs and male infertility.